Characterization of AlInN/GaN based HEMT for Radio Frequency Applications - Prasad, Santashraya; Islam, Aminul (Micro and Nanosystems, 2023)
Background: The Si- and GaAs-based devices are not suitable for very high-speed and high-power applications. Therefore, GaN-based devices have emerged as a potential contender. Further improvement in the device characteristics using appropriate mole fractions of Al and InN in the barrier layer of AlInN has become inevitable. Objective: To design AlInN/GaN HEMT and present its salient features. Methods: The design method for the proposed AlInN/GaN HEMT includes a selection of materials, optimization of mole fraction in AlInN barrier layer, optimization of gate oxide thickness, optimization of device dimensions, and doping concentration. The fabrication steps necessary for the AlInN/GaN HEMT are also explained in the paper. Analysis of the structure has been carried out using the Silvaco TCAD tool. Results: All the obtained results have revealed that the proposed device can operate up to the cut-off frequency of 102 GHz and a maximum oscillation frequency of 230 GHz, which are suitable for radiofrequency applications. The minimum noise figure and maximum transducer power gain ( 18 dB) achieved by the proposed device is quite acceptable. Conclusion: The use of the AlN spacer layer has improved the AlInN film quality and mitigates strain at the heterointerface. Moreover, it reduces the Coulomb attraction between ions in the supply layer and electrons in the channel layer thereby improving carrier mobility. Usage of a SiO2 layer between the gate and AlInN barrier layer has decreased the gate leakage current. This has reduced the subthreshold slope and increased ON/OFF current ratio ( 1010). The proposed Si3N4 passivated HEMT offers a breakdown voltage of 1395 V.
Keywords: subthreshold